Disposable carrier for retrograde fillings - Ngeow, Wei Cheong; Chai, W.L. (2006)
Commercially available retrograde filling carriers are delicate and easily damaged by pressure. In addition, they are difficult to clean and keep free from blockage. This report describes a simple and easy technique for transforming a standard disposable hypodermic syringe and needle into a disposable carrier for retrograde fillings. Â© 2006 Asian Association of Oral and Maxillofacial Surgeons.